Personhood in Classical and Process-Oriented Metaphysics - Bracken, Joseph A. (Horizons, 2014)
One major source of conflict in contemporary sexual ethics (e.g., artificial contraception and abortion) is the implicit difference in the worldviews represented by the terms "pro-life" and "pro-choice." Those who are pro-life support the notion of human personhood as a fixed and unchanging reality from conception to death; those who are pro-choice, in contrast, support the notion of human personhood as developmental, never fully realized. The pro-life position basically reflects the worldview of classical metaphysics; the pro-choice position is logically grounded in process philosophy and theology. The aim of the present article is to compare and contrast these two worldviews so as to see whether or not there is unexpected common ground between the two that could logically justify a consensus position on the more specific moral issues.